Reliability of the i-STAT for the determination of blood electrolyte (K+, Na+, and CI-) concentrations in cattle - Yildirim, E.; Karapinar, T.; Hayirli, A. (Wiley-Blackwell, 2015)
Background: Rapid determination of blood electrolyte concentrations can help determine electrolyte status and delivery of effective volume of electrolyte solutions in field conditions. Objective: To evaluate reliability of the i-STAT, a point-of-care (POC) device, in measuring blood K+, Na+, and CI- concentrations in cattle. Animals: Ninety-eight cattle with various diseases. Methods: In this prospective study, blood samples collected from the jugular vein were processed for determination of K+, Na+, and CI- concentrations in blood and plasma using the i-STAT and auto-analyzer (Cobas C501), respectively. Blood and plasma electrolyte data were subjected to student t-test for comparison, the concordance analysis for agreement, accuracy, and precision, the Passing-Bablok regression and the Bland-Altman plot for reliability, and receiver operating characteristics curves for sensitivity (Se) and specificity (Sp). Results: Plasma concentrations of K+ (4.39 versus 4.2 mmol/L; P <.0001) and CI- (100.30 versus 99.4 mmol/L; P <.04) were greater than their concentrations in blood. Plasma and blood Na+ concentrations were similar (136.95 versus 136.8 mmol/L). The i-STAT results were highly correlated with the Cobas C501 results (r = 0.970, 0.922, and 0.866 for K+, Na+, and CI-, respectively). Regression equations fitting blood (Y) and plasma (X) concentration did not deviate from the identity line for K+ (Y = - 0.10 + 0.98 9 X), Na+ (Y = X), and CI- (Y = 3.04 + 0.96 9 X). The mean bias (blood concentration -plasma concentration) was - 0.20 for K+ (P =.03), -0.16 for Na+ (P = .12), and -0.87 for CI- (P = .93). The i-STAT had 76-100% Se and 87.7-100% Sp for assessing electrolyte statuses. Conclusions and Clinical Importance: The i-STAT yielded results that were in agreement with the auto-analyzer, with negligible biases in measurement of plasma K+, Na+, and CI- concentrations. The i-STAT is a reliable POC device and can be used in field condition to assess electrolyte status in cattle.
Keywords: Accuracy; Bovine; Point-of-care device; Precision; Sensitivity; Specificity